Representations of Gender in English Textbook Super Minds: A Critical Discourse Analysis - Khairunnisa Fitri Nasution; Eddy Setia; Rahmadsyah Rangkuti (JEELS (Journal of English Education and Linguistics Studies), 2025)
Gender stereotypes that are developed in the society influence people’s thoughts and behavior. Schools contribute the socialization of gender through textbooks or interaction between teachers and students. Textbooks are extremely important in forming students' values, ideologies, and social norms. They are also acknowledged for having a major impact on how students' gender roles develop, especially in elementary school. Language use and social lives of pupils may be impacted by gender representation. The textbook material they study accounts for half of the influence. Children have access to a wealth of knowledge regarding behavior, characteristics, and social roles that are proper for each gender that are portrayed in textbooks. This research was aimed to see how gender represented according to the three social context parameters such as family, occupation, and leisure activities were used to perform Examining the gender portrayals of male and female characters in the Super Minds 6 English textbook. This research used qualitative and quantitative research methods and employed Fairclough's Critical Discourse Analysis (CDA) theory as the method of analysis. In conjunction with CDA, Giaschi's Visual Grammar theory is also used as an analytical tool to explain the depiction of gender representation in the textbook. Based on the findings, there are more male pictures than female pictures.